Beyond Human Dominion: Qur’anic Ecotheology and the Ethics of Environmental Accountability in Tafsir Studies - Muhammad Ikbar Rozaqi; Ahmad Nurrohim (JURNAL ISLAM NUSANTARA, 2025)
The contemporary environmental crisis, marked by ecosystem degradation, pollution, and the unsustainable exploitation of natural resources, reveals a profound ethical rupture in the human–nature relationship. Within Muslim societies, this crisis reflects a failure to internalize religious values that define humanity’s normative role as khalifah fi al-arḍ (vicegerent on earth). This study aims to examine how ecological concepts are articulated in the Qur’an through tafsir literature and to formulate a framework of ecological piety grounded in Islamic theology. Employing a qualitative library-based research design, the study analyses selected classical and contemporary Qur’anic exegeses using a thematic analysis. Primary tafsir sources are examined alongside relevant scholarly works in Islamic theology and environmental studies to ensure analytical depth. The findings reveal three interrelated dimensions of Qur’anic ecotheology. First, humans are positioned as divine trustees responsible for maintaining ecological balance and sustainability. Second, nature is conceptualised as ayat kawniyyah, cosmic signs that cultivate spiritual awareness and ethical responsibility. Third, environmental destruction is interpreted as a moral transgression that entails divine accountability and consequences. This study contributes a tafsir-based framework of ecological piety that enriches Islamic environmental ethics and contemporary ecotheological discourse. It recommends further empirical research to explore the application of this framework in Islamic education and environmental policymaking.